2007
DOI: 10.1103/physrevlett.98.206105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ice Structure on Ultrafast Electron Dynamics inD2OClusters on Cu(111)

Abstract: The structure of D2O clusters on a Cu(111) surface and the femtosecond dynamics of photoexcited excess electrons are investigated by low-temperature scanning tunneling microscopy and two-photon photoemission spectroscopy. Two types of amorphous ice clusters, porous and compact, which exhibit characteristic differences in electron dynamics, are identified. By titration with Xe we show that in both structures solvated electrons preferentially bind on the cluster surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 18 publications
3
49
0
Order By: Relevance
“…We now discuss the time-dependent evolution of the binding energy and the population decay, which has been observed in the fs to ps range at amorphous ice-metal interfaces 24,34,40 and in liquid water, 42 where it has been attributed to dynamical screening during the solvated electron formation. However, for crystalline ice on Ru(001), we observe a localized state (e T ) stabilized by 1 eV with respect to the delocalized state (n ) 1) ( Figure 3).…”
Section: Thermally Activated Relaxation Among Conformational Substatesmentioning
confidence: 99%
“…We now discuss the time-dependent evolution of the binding energy and the population decay, which has been observed in the fs to ps range at amorphous ice-metal interfaces 24,34,40 and in liquid water, 42 where it has been attributed to dynamical screening during the solvated electron formation. However, for crystalline ice on Ru(001), we observe a localized state (e T ) stabilized by 1 eV with respect to the delocalized state (n ) 1) ( Figure 3).…”
Section: Thermally Activated Relaxation Among Conformational Substatesmentioning
confidence: 99%
“…The ultrafast dynamics of electrons photoinjected into thin water-ice films on metal substrates were studied in detail by Bovensiepen and co-workers. [7][8][9] They found that electron transfer from the optically excited substrate into the ice conduction band was followed by solvation leading to electron localization on an ultrafast time scale. The solvated electrons were reported to have picosecond lifetimes, mainly limited by tunneling back to the metal substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, the electron lifetime was found to be morphology dependent, with evidence that the electron was localized at the ice-vacuum interface for water-ice clusters on metal substrates. 9 Sanche and co-workers studied the effect of electron attachment to water-ice films following lowenergy electron bombardment. 3,10,11 They found that the solvated electrons formed following attachment from the gas phase have relatively long lifetimes, and support a variety of chemical reactions, including dissociative electron attachment to halocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 UHV studies of electron population dynamics, energy relaxation, band structure and localization phenomena are commonplace for a large variety of metal-dielectric interfaces using two-photon photoemission (2PPE). [17][18][19][20][21] 2PPE can access interfacial electronic states and track the dielectric response of adsorbed thin films. A sub-hundred femtosecond pulse and its second harmonic impinge upon an Ag substrate with a controllable time delay of femtoseconds to picoseconds between pulses.…”
Section: Introductionmentioning
confidence: 99%